C-reactive protein velocity predicts microvascular pathology after acute ST-elevation myocardial infarction. (14th October 2021) - Holzknecht, M; Tiller, C; Reindl, M; Lechner, I; Troger, F; Mayr, A; Brenner, C; Klug, G; Bauer, A; Metzler, B; Reinstadler, S
Abstract: Background: The role of C-reactive protein velocity (CRPv) as an early and sensitive marker of an excessive inflammatory response in the setting of acute ST-elevation myocardial infarction (STEMI) is only poorly understood. Purpose: The aim of this study was to investigate, in patients with STEMI treated with primary percutaneous coronary intervention (PCI), the association of CRPv with microvascular infarct pathology. Methods: This prospective cohort study included a total of 316 patients with STEMI undergoing PCI. CRPv was defined as the difference between CRP 24±8h and CRP at hospital admission, divided by the time (in h) that have passed during the two examinations. The association of biomarker levels with cardiac magnetic resonance (CMR)-determined microvascular obstruction (MVO) was evaluated. CMR was performed at a median of 3 [interquartile range 2–4] days after PCI. Results: After adjustment for cardiac troponin T (cTnT), culprit lesion location and TIMI-flow post-PCI, CRPv (odds ratio 3.36, 95% confidence interval (CI) 1.72–6.57; p<0.001) remained significantly associated with the occurrence of MVO. CRPv (area under the curve [AUC] 0.76, 95% CI 0.71–0.81; p<0.001) was a better predictor for MVO compared to 24h CRP (AUC difference: 0.03, p=0.002). The addition of CRPv to peak cTnT resulted in a higher AUC for MVO prediction than peak cTnT alone (AUC 0.86, 95% CI 0.82–0.90; p<0.001 vs. AUC 0.84, 95% CI 0.79–0.88; p<0.001. AUC difference: 0.02, p=0.042). Conclusions: In patients with STEMI treated with primary PCI, CRPv was associated with microvascular infarct pathology with a predictive value incremental to cTnT, suggesting CRPv as an early and sensitive biomarker for more severe infarct pathology and outcome. Funding Acknowledgement: Type of funding sources: None.